Evaluating the Sustainable Growth of Small- and Medium-Sized Construction Enterprises Using the Multicriteria Decision-Making Method. (9th September 2020) - Wang, Wenbao; Lin, Wenhe; Dai, Xinyi; Yan, Yingzheng; Xuan, Aiping
Abstract : Sustainable growth plays an important role in the development of small- and medium-sized construction enterprises and has increasingly become a hot topic in the political and academic arenas. Growth is an important indicator for measuring the operational status and development potential of listed enterprises and is of great significance for studying sustainable growth. Considering the development of small- and medium-sized construction enterprises, a growth evaluation index system that includes growth resources, growth ability, and growth innovation was established, and a growth evaluation model was constructed using the improved entropy-VIKOR algorithm. Evaluation and analysis of the sustainable growth of small- and medium-sized construction enterprises listed before the end of 2012 were conducted. The parameter sensitivity, weight sensitivity, and effectiveness of the evaluation model were analysed. The empirical results showed that compared with the TOPSIS method and the traditional VIKOR method, the multicriteria evaluation model for the sustainable growth of small- and medium-sized construction enterprises proposed in this paper had better stability and effectiveness. Finally, the key influencing factors, growth ranking, and dynamic growth types of small- and medium-sized construction enterprises were analysed, and targeted suggestions were proposed. The research results can provide a reference for managers, investors, and regulators.